Histochemical study of the extensor digitorum longus and soleus muscles in alcoholic rats - Torrejais, M. M.; Soares, J. C.; Matheus, SMM; Cassel, F. D.; Curi, P. R. (Blackwell Wissenschafts Verlag Gmbh, 1999)
The extensor digitorum longus (EDL) and soleus (SOL) muscle fibres from albino rats submitted to experimental chronic alcoholism were evaluated in accordance with their metabolic and morphometric profiles. Twenty-seven male animals aged 4 months and weighing approximately 400 g were used. The animals were divided into three groups: control, isocaloric and alcoholic and sacrifices were carried out after 5, 10 and 15 months. The muscles were dissected, removed, cross-sectioned in a cryostat and submitted to the NADH (nicotinamide adenine dinucleotide) reaction. The SO (slow-twitch-oxidative), FG (fast-twitch-glycolytic) and FOG (fast-twitch-oxidative-glycolytic) muscle fibre types exhibited a polygonal, triangular or rounded shape and did not present noteworthy modifications in either muscles during the study. The cross-sectional areas of the fibres from the studied muscles did not present significant differences during the observations. Fibre area behaved similarly in the alcoholic animals up to the 10th month, i.e. it was decreased, as also observed in the other groups. At 15 months, however, all fibres were increased, with a predominance of FG fibres in the SOL muscle. Changes in fibre population were observed mainly in the SOL muscle of alcoholic animals: SO fibres were initially increased in number but decreased after the 10th month, and the opposite was observed for the population of FG fibres. FOG fibres increased linearly in number throughout the experiment. The statistical analysis showed nevertheless that the fibre population and cross-sectional area changes were not significant. In the alcoholic animals quantitative variations of muscle fibres were more evident in the SOL muscle, suggesting that the SOL muscle is more sensitive to the toxic action of ethanol. The results concerning the increased fibre diameter in alcoholic animals would be associated with muscle oedema induced directly or indirectly by the ethanol.